Statistical evaluation of pre-selection criteria for industrialized building system (IBS) - Azman, Mohamed Nor Azhari; Ahamad, Mohd Sanusi S.; Majid, Taksiah A.; Yahaya, Ahmad Shukri; Hanafi, Mohd Hanizun (Journal of Civil Engineering and Management, 2014)
The Malaysian government has endorsed the use of an industrialized building system (IBS) in domestic projects. These have shifted the focus of the nation's construction industry towards mass production and modular products. A proper study on site selection criteria for new IBS precast manufacturing sites has now become essential. The preliminary study in this research determines the IBS precast manufacturing site selection criteria from literature reviews. Questionnaires pertaining to IBS acceptance and preference criteria were send to manufacturers, policymakers, academicians and contractors. The outcome analyses the respondents’ view towards 15 site selection criteria. The result from the ANOVA statistical test indicates that most respondents agreed with the selected criteria except political and regulation criteria, urban requirement criteria, and personal criteria. However, there is a significant difference within the opinions of the contractors and manufacturers sector. Likewise, the mean ranking analysis of criteria shows significant difference in their preferences. The ideal rank of criteria preferred by the correspondents are costs, transportation and optimum distance, land sites, resources and utilization, infrastructures, economy markets, labour, inter-industry linkage, environmental risk, competition, personal, population, capacity, political and regulatory, and urban criteria.